Fanatic about Phonetics - Mahesan Baskaran, Loga (Journal of Modern Languages, 2017)
This paper is a reprinted speech from the conference of phonetics in October 1983, attended in the University of Malaya (UM), Malaysia. The paper compares the phonetics in both Bahasa Malaysia and English.